A study of blood product use in patients with major trauma in Scotland: analysis of a major trauma database. Issue 5 (23rd April 2007) - McRoberts, Randal J; Beard, D; Walsh, T S
Abstract : Objectives: (1) To define blood product requirements in patients with trauma whose underlying injuries are consistent with major blood loss; (2) to use these data to estimate the annual number of patients in Scotland who sustain significant trauma and require substantial blood product replacement; and (3) to place these data in the context of recent findings concerning the efficacy of recombinant factor VIIa in patients with major trauma. Methods: A retrospective casenote review study was conducted for patients who presented with trauma at each of four Scottish hospitals. The four sites were selected from the 26 hospitals that were the source of data for the Scottish Trauma Audit Group (STAG) database. Collected between 1991 and 2002, STAG encompasses approximately 53 000 patients. 129 patients whose trauma codes were likely to be linked to injuries associated with major blood loss were selected. Data on the use of blood products for each patient were collected and analysed for three periods: (1) time spent in the emergency department (ED); (2) time from leaving the ED to the end of the first 24 h; and (3) time from the end of the first 24 h to 7 days. Blood product use for each period and for the entire first week of care was described for all patients and for blunt and penetrating injury subgroups. Using national population data estimates, the incidence of major trauma requiring blood transfusion was calculated for Scotland. Results: Among the patients with trauma codes predicting significant blood loss, the proportion of patients requiring any blood transfusion within the first 7 days was 53.9%. 27.4% of patients received ⩾8 units of red cell concentrate (RCC) within the first 24 h of hospitalisation. By direct extrapolation, we estimated that the annual number of Scotland's patients (aged >13 years) with a significant blood transfusion requirement secondary to traumatic injury was 67. Of these, 35 patients would require ⩾8 units of RCC within the first 24 h. Conclusion: In summary, this study estimates that approximately 67 patients annually in Scotland, above the age of 13 years, require blood transfusion as a direct result of significant traumatic injury. Of these 67 patients, an estimated 35 patients (28 of whom had a blunt form of trauma) require ⩾8 units of RCC during the first 24 h in hospital. On the basis of the current limited trial evidence, the potential benefit in using recombinant factor VIIa in such patients, in Scotland, is small—approximately seven patients per million population aged >13 years, per year.